Nutritional Status and Weight of Pregnant Women to Birth Weight (BBL) to Early Detection of Stunting - Mulianingsih, Misroh; Nurmayani, Winda; Pratiwi, Eka Adithia; Safitri, Rifky Noviana; Hayana, Hayana (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One of the factors that influence fetal growth during pregnancy includes the mother’s nutritional status at the beginning of pregnancy and the mother’s weight gain during pregnancy and delivery,such as;stunted fetal growth (PJT).Low birth weight (LBW),small,short,thin,low immune system,and risk of death.The purpose of this study was to determine the relationship between nutritional status and body weight of pregnant women on birth weight (LBW) in the context of early detection of stunting in the working area of ​​Penimbung. This type of research is Cohort survey with a prospective approach, sampling 30 respondents using total sampling technique.Data collection using observation sheet instrument.The results of the chi-square test showed that the nutritional status was obtained. p-value = 0.538> 0.05, and the maternal body weight obtained p-value = 0.474> 0.05, it means that the results of the analysis of all data, both nutritional status and weight, did not show a significant value. P-value> 0.05